PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V PADA MATERI PERISTIWA ALAM - Handayani, Lastri; Sujana, Atep; Sunarya, Dede Tatang (Jurnal Pena Ilmiah, 2017)
Research is calledÂ  problem based learning to improve the ability to critial thinking studentsgrade 5 to the matter of natural events. The study is done at high students group, and, and low, in order to see how increased capacity critical thinking students. Method in this research that is uses the method pre-eksperimen with the design pre-eksperimen group one-group pretest-posttest. Population to research it is a whole primary school sub district pabuaran who ranks school including the sand from SDN 1 Pabuaranlor. An instrument used is about tests the ability of critical thinking, sheets of observation, and chief. The results of the study with of significance in áµ… = 0.05 show that there is an increase in the capacity to think critical students on high group, and, and low. Thus, so the capacity to think critical students on high group, and, and low happened an increase in .